1989
DOI: 10.1128/iai.57.5.1438-1444.1989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Campylobacter jejuni infection in Macaca nemestrina

Abstract: Experimental infection of four specific-pathogen-free Macaca nemestrina monkeys (aged 3.5 and 4.5 months) with Campylobacterjejuni 81-176 caused acute diarrheal illness, characterized by fluid diarrhea, bloody stools, and fecal leukocytes, which lasted for approximately 7 to 11 days. Histologic examination of intestinal biopsies showed acute colitis characterized by infiltration of the mucosa with neutrophils and lymphocytes, and cryptitis. There were no histologic changes in the small intestine. Excretion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 23 publications
4
39
0
Order By: Relevance
“…The effect is even greater when both complement and immune serum are present. This is in agreement with the previously published in vivo investigations [8,14]. Opsonization also increased stimulation of PMNs, as shown in animal models [8].…”
Section: Discussionsupporting
confidence: 93%
“…The effect is even greater when both complement and immune serum are present. This is in agreement with the previously published in vivo investigations [8,14]. Opsonization also increased stimulation of PMNs, as shown in animal models [8].…”
Section: Discussionsupporting
confidence: 93%
“…and an isogenic pspA mutant to cause disease in a modification of the ferret disease model ( Table 5). The wild-type strain causes a moderate to severe diarrhoea in this model, with green mucoid stools, often with occult or frank blood, consistent with symptoms observed when 81-176 was fed to humans (Black et a/., 1988) or primates (Russell et a/. , 1989).…”
Section: Discussionsupporting
confidence: 73%
“…Studies in the IPRL investigating the prevalence of Campylobacter infection indicated that 70% of infants housed in the lab were infected by at least one strain of Campylobacter by 18 months of age [Russell et al, 1988]. A prospective study of Campylobacter infection was conducted on four infants (3 1 /2 to 4 1 /2 months old) that were specific pathogen free for both Campylobacter and Shigella [Russell et al, 1989]. These infants were experimentally infected with two Campylobacter jejuni serotypes that were obtained from outbreaks of human C. jejuni infections [Blaser et al, 1979;Glass et al, 1983].…”
Section: Campylobactermentioning
confidence: 99%